Optimal Allocation and Sizing of Capacitor Banks in Distribution System to Reduce the Power Loss Using Beluga Whale Optimization - Sitotaw Mengesha Adal; Ermiyas Tesfakiros Reda (International Transactions on Electrical Energy Systems)
One portion of the distribution system is the distribution feeder. Buses carrying more loads and having long-distance route lines are significant problems due to the presence of power loss and the increase in the overall cost of the transportation process. Hence, the overall power loss minimization is taken as the major objective. The best sizing and allocation of capacitors in a bank in the distribution line are used to minimize the total loss. BWO technique is utilized in this optimization process. The backward-forward sweep load flow is used for the computation of the power flow in MATLAB. The sensitive buses have been chosen according to the factor of loss sensitivity (LSF) and using BWO. The validity of the test has been made on the standard IEEE 34 and 85 bus radial distribution system. The simulation results in the 34-bus radial system are much different from the results of PSO, GWO, WO, and IWO. In the 85-bus radial system, the results are seen with the outcomes of PSO, WO, and BFOA. In both cases, the results of the proposed technique are found to be better than the existing methods. Therefore, the result shows that BWO can be effective for future selection to improve large distribution networks by sizing and locating the capacitors optimally.